Lead and Mercury Exposure and Related Health Problems in Metal Artisan Workplaces and High-Risk Household Contacts in Thimphu, Bhutan - Adeep Monger; Karma Wangdi (The Scientific World Journal)
Background. Metal artisans have been using lead and mercury in their settings for centuries. Exposure to these toxic heavy metals causes adverse health effects. We assessed the occupational exposure of metal artisans and their high-risk household contacts at Thimphu, Bhutan. Methods. A cross-sectional study in which 134 metal artisan center employees and 48 high-risk household contacts were tested for blood lead and mercury levels. Sociodemographic data, occupational exposure risk factors, and clinical syndrome related to lead and mercury exposure were further obtained and analyzed using EpiInfo 7.0. Results. The mean age of the metal artisan center employees was 36.02 ± 10.3. The prevalence of elevated blood lead and mercury level was 38.4% and 51.9%, respectively. Significantly higher prevalence of mercury level was observed among the artisans compared to nonartisans (66.97 vs, 16.0). Among three centers, the goldsmith section of the Department of National Properties had the highest (94.1%). Profession as an artisan, mold designing, performing gold amalgamation, working for >8 hours a day, working for >5 years, and working at home were significant risk factors associated with elevated blood mercury level. Significant association was observed between elevated mercury level and complaints of burning or watery eyes (p=0.001), anxiety, nervousness, irritability, severe shyness (p=0.029), muscle aches (p=0.019), and stomach cramps or pain (p=0.009). Conclusion. The prevalence of elevated blood mercury level is concerning among the artisans. Advocacy, proper usage of personal protective equipment, awareness on chemical safety, and hazard associated with lead and mercury usage are needed to minimize the exposure.